Finance-induced Innovation: A New Mechanism Explaining Finance-Inequality Relationship - Zhu, Xiaoyang; Kuo, Ying-Min (Journal of Income Distribution®, 2022)
This paper uncovers a new mechanism through which financial development affects in- come inequality. We first revisit the effect of financial development on inequality using a panel of 94 countries from 1980 to 2017. The results show that both credit and equity markets development are positively related to different measurements of inequality, and the results are robust to endogeneity tests and other specifications. We then show empirically that this positive finance-inequality relationship can be explained by finance-induced innova- tion, especially by the finance-induced high-technology innovation. We further find that this mechanism seems to be more important than other innovation-related factors in explaining the finance-inequality relationship in low- and middle-income countries.